2016
DOI: 10.1016/j.bpj.2016.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Clustering Digitizes Biochemical Signaling and Enhances its Fidelity

Abstract: Many membrane-bound molecules in cells form small clusters. It has been hypothesized that these clusters convert an analog extracellular signal into a digital intracellular signal and that this conversion increases signaling fidelity. However, the mechanism by which clusters digitize a signal and the subsequent effects on fidelity remain poorly understood. Here we demonstrate using a stochastic model of cooperative cluster formation that sufficient cooperation leads to digital signaling. We show that despite r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…On average clusters consisted of around 13 molecules. Incidentally, this cluster size is very similar to the size of clusters providing optimal fidelity in digital signalling as reported in a theoretical study31. For higher Ca 2+ concentrations, [Ca 2+ ] i  ≈ 20 μM, and after long exposure to an increased Ca 2+ concentration, the mean number of molecules in a cluster was essentially the same as for the lower Ca 2+ concentration (Fig.…”
Section: Resultssupporting
confidence: 86%
“…On average clusters consisted of around 13 molecules. Incidentally, this cluster size is very similar to the size of clusters providing optimal fidelity in digital signalling as reported in a theoretical study31. For higher Ca 2+ concentrations, [Ca 2+ ] i  ≈ 20 μM, and after long exposure to an increased Ca 2+ concentration, the mean number of molecules in a cluster was essentially the same as for the lower Ca 2+ concentration (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Dynamic molecular clusters can form through weak binding interactions between multivalent molecules. They are highly plastic structures with a distribution of stoichiometries and sizes; they are becoming increasingly recognized as molecular platforms to drive key cellular functions, especially receptor-mediated signaling (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). For example, the epidermal growth factor receptor (EGFR) dimerizes and develops kinase activity when it binds its ligand, resulting in multiple phosphorylated sites on the cytoplasmic domains; these in turn interact with multiple SH2 domains on other multivalent scaffold or adaptor proteins, which then recruit additional binding partners (13).…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies showed that Ras dimerization activates the MAPK pathway and therefore likely plays an important role in signal transduction. Similarly, a role for dimerization and nanocluster formation in signaling (Solman et al, 2015;Roob et al, 2016), possibly due to orientation changes of the G-domain (Mazhab-Jafari et al, 2015), was also reported by other groups. Specifically, Muratcioglu et al (2015) reported that K-Ras dimer formation is nucleotide dependent using dynamic light scattering and nuclear magnetic resonance (NMR) spectroscopy.…”
Section: Membrane Binding Of Rasmentioning
confidence: 67%